68 PREDICTORS OF SUCCESSFUL PESSARY FITTING AND CONTINUED USE IN A NURSE-MIDWIFERY PESSARY CLINIC. (1st January 2006) - Maito, J. M.; Quam, Z. A.; Danner, K. A.; Craig, E.; Rogers, R. G.
Abstract : Objective: To identify predictors of successful pessary fitting and continued use. Methodology: Women with incontinence and/or pelvic organ prolapse presenting to a urogynecology service were offered referral to a dedicated midwifery pessary clinic. Charts of these women were reviewed for demographic information, physical exam, pelvic floor disorders, and details of pessary fitting sessions. Successful fitting was defined as a comfortable fit and retention of the pessary with Valsalva and voiding. Continuation was defined as a successfully fitted patient who returned at least once following the initial fitting with the pessary still in use. Spearman's correlations identified variables associated with successful fitting and continuation of use. Logistic regression identified variables that predicted continued use. Results: Eighty six percent (103/120) of women were successfully fitted and 92/103 (89%) continued use of their pessary for a mean of 6 months. Predictors of unsuccessful fitting included a history of a prior prolapse procedure or hysterectomy ( p ≤ .001). Severe posterior prolapse was associated with pessary discontinuation after adjustment for patient's age ( p < .04). Success rates for treatment of stress urinary incontinence (SUI), pelvic organ prolapse (POP), or both were not significantly different (percent success 94, 89, 81 respectively, p = .50). Conclusion: Predictors of unsuccessful pessary fitting include history of a prior prolapse procedure and hysterectomy. Severe posterior prolapse was the single predictor of pessary discontinuation.